2022
DOI: 10.1111/bph.15907
|View full text |Cite
|
Sign up to set email alerts
|

d‐Pinitol promotes tau dephosphorylation through a cyclin‐dependent kinase 5 regulation mechanism: A new potential approach for tauopathies?

Abstract: Background and Purpose: Recent evidence links brain insulin resistance with neurodegenerative diseases, where hyperphosphorylated tau protein contributes to neuronal cell death. In the present study, we aimed to evaluate if D-pinitol inositol, which acts as an insulin sensitizer, affects the phosphorylation status of tau protein.Experimental Approach: We studied the pharmacological effect of D-pinitol on insulin signalling and tau phosphorylation in the hippocampus of Wistar and Zucker rats.To this end, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…However, the presence of fructose demands more studies to clarify the potential unwanted side effects derived of the repeated consumption of carob syrup. The additional preclinical studies designed have addressed most of these potential problems, as well as added more information regarding the recently described properties of D-Pinitol [25,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of fructose demands more studies to clarify the potential unwanted side effects derived of the repeated consumption of carob syrup. The additional preclinical studies designed have addressed most of these potential problems, as well as added more information regarding the recently described properties of D-Pinitol [25,41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, D-pinitol (DPIN), a naturally occurring inositol capable of activating the insulin pathway in peripheral tissue, has also been reported to improve insulin-resistance-associated disorders in the brain. D-pinitol lowered tau phosphorylation by regulating cyclin-dependent kinase 5 (CDK5) activity in mouse brain [ 97 ] and activated the insulin signaling pathway by increasing the phosphorylation of PI3K/Akt in rat hypothalamus [ 98 ], suggesting D-pinitol as a potential drug for the treatment of neurological disorders such as dementia.…”
Section: Mechanisms Of Hypoglycemia Induced Dementia In Patients With...mentioning
confidence: 99%
“…Insulin resistance contributes to the occurrence and worsening of symptoms of neurodegenerative diseases, so D-pinitol as an insulin sensitizer can play an important role in the inhibition of brain alterations. Medina-Vera et al have shown that oral supplementation of D-pinitol lowered tau phosphorylation, by regulating cyclin-dependent kinase 5 (CDK-5) activity [117]. Scyllo-inositol, as mentioned above, is another naturally occurring stereoisomer of MI and it is also considered a potential remedy for neurodegenerative diseases.…”
Section: Itselfmentioning
confidence: 99%